Letter from R.E. Preston to Margaret M. Booth, April 20, 1889 - Preston, Robert E., 1836–1911 (1889)
Letter from Robert E. Preston (1836-1911), of the United States Mint Bureau, to Margaret M. Booth née Cardeza informing her that he failed to see a bill to relieve James Booth's estate of its assessment for missing silver bars. Preston then discusses the difficulty of getting any sort of private relief bill, other than pensions, through Congress.
Keywords: Booth, James Curtis, 1810-1888; Bills, Legislative; Martinez Cardeza, Margaret; Preston, Robert E., 1836–1911; United States Mint; Mint of the United States